Os produtos universitários e suas contribuições para o desenvolvimento regional: uma perspectiva dos atores regionais - Safa, Kauana Nassin (2021)
The role of Higher Education Institutions HEIs, in the regional development process gained relevance from studies based on the implementation of a third mission, identifying how university entrances and exits contribute to this process. The models identified in this dissertation, mostly, study aspects of economic contributions and depart from the view that HEIs have about their own deliveries, treated here as university products. It is very complex to measure the contributions that HEIs offer to the regions, due to the large number of actors involved in the process. Through a bibliographic survey to identify university products and the analysis of theoretical models used to understand these contributions, this dissertation uses the model of Ramos Filho (2020), using the vision of regional actors for the development of the study. The objective of the dissertation is to analyze the contributions of university products delivered by private HEIs in Foz do Iguaçu in the development of the region. The research is of a qualitative nature and had the geographic nature of the 9th regional of the West of Paraná. Four questionnaires were applied electronically to private HEIs in the city of Foz do Iguaçu PR, with the purpose of identifying the university products they deliver and the regional actors with which they relate. After identifying the actors, 8 interviews were carried out to understand their view of the contributions that university products bring to the region. Data analysis was performed using software encodings, data triangulation and subsequent content analysis. The results reveal a positive understanding of regional actors in relation to university products generated by private HEIs, the organization between HEIs, actors and regional demands, but point out aspects of greater contribution to a study of local development than the regional one, even these products indirectly benefit the region.